Governance and Transparency: A Case of Pakistan - Batool, Atiqa; Asmat, Khadija; Muzaffar, Muhammad (Annals of Human and Social Sciences, 2023)
This study aims to emphasize the significance of Governance and Transparent Political Process in Pakistan. Governance is commonly known for providing tasks and duties, so that the government must complete it on behalf of the governed people. The research is conducted using qualitative approach and focus on the core principle of good governance that is Transparency. In Pakistan, there is typically a lack of transparency on the use of power by the authorities. The absence of a sufficient transparent framework allows the government to abuse citizens’ rights. This study reveales the inefficiency of democratic institutions that are not providing transparency and openness in their affairs. In Pakistan, Governance becomes effective only if they are made people aware of governmental policies, meetings and decision making. In order to ensure openness and make information from public records accessible to the general public, the government must carry out activities and establish policies.